Greta Garbo and Clarence Brown: An Analysis of their Professional Relationship in the Context of Classical Hollywood Cinema - Guiralt, Carmen (Arte, Individuo y Sociedad, 2020)
This article consists of a study of the professional relationship between Greta Garbo and Clarence Brown, her most regular Hollywood director, who directed her in seven feature films—no other filmmaker directed her in more than two—and whom film critics and historians have invariably indicated as her “favourite director”. Although in the late twenties and during the first half of the thirties the Garbo-Brown duo was considered the most successful actress-director team of the time, their association is virtually unknown today. Was Brown really, as so often stated, her “favourite director”? What was the reason for Garbo’s reluctance to repeat with the same filmmaker more than twice? Why did she allow Brown to direct her in seven films? What was his success in directing her? Was Garbo a technical or instinctive actress? Was she a great performer or simply endowed with a magnificently photogenic face? In order to uncover the answers to these questions, an in-depth chronological analysis has been undertaken of their seven joint films, made over an eleven-year period of collaboration, by consulting a wide range of period and contemporary sources, in addition to an unpublished interview with the director.